2012
DOI: 10.1016/j.molbiopara.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania parasites possess a platelet-activating factor acetylhydrolase important for virulence

Abstract: Leishmania parasites are intracellular protozoans capable of salvaging and remodeling lipids from the host. To understand the role of lipid metabolism in Leishmania virulence, it is necessary to characterize the enzymes involved in the uptake and turnover of phospholipids. This study focuses on a putative phospholipase A2 (PLA2)/platelet-activating factor acetylhydrolase (PAF-AH) in L. major. In mammals, PAF-AH is a subgroup of PLA2 catalyzing the hydrolysis/inactivation of platelet-activating factor (PAF), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Leishmania species, an intracellular protozoan, expresses PAF-AH, which appears to play a key role in virulence of the organism. 112 It is clear that the PAF signaling pathway is fundamental to a number of pathologic processes, and therefore control of this pathway should hold great promise in the therapeutic arena. We are still in the early stages of understanding PAF signaling, and further investigation of its role in pathology and therapeutic modulation is highly anticipated.…”
Section: Paf: Emerging Roles and Future Directionsmentioning
confidence: 99%
“…Leishmania species, an intracellular protozoan, expresses PAF-AH, which appears to play a key role in virulence of the organism. 112 It is clear that the PAF signaling pathway is fundamental to a number of pathologic processes, and therefore control of this pathway should hold great promise in the therapeutic arena. We are still in the early stages of understanding PAF signaling, and further investigation of its role in pathology and therapeutic modulation is highly anticipated.…”
Section: Paf: Emerging Roles and Future Directionsmentioning
confidence: 99%
“…This PE N-methylation pathway is the predominant PC synthesis route in hepatocytes 31 and Saccharomyces cerevisiae 32 , but is absent in Trypanosoma brucei 33,34 . Additionally, Leishmania can directly take up lipids including glycerophospholipids from the host or media and then remodel them into parasite-specific lipids 35–38 . So why would Leishmania parasites retain multiple, seemingly redundant PC synthesis pathways (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In different pathogenic microorganisms (including bacteria and protozoa) PLA 2 activity is important for the pathogen interaction with host cells (Connelly and Kierszenbaum, 1984;Saffer and Schwartzman, 1991;Silverman et al, 1992). In Leishmania, different studies showed the presence of PLA 2 activity in L. amazonensis and of a platelet-activating factor acetylhydrolase (PAF-AH) in L. major (Henriques et al, 2003;Passero et al, 2008;Pawlowic and Zhang, 2012). Unlike that reported by Passero et al (2008), we showed here that most PLA 2 activity in L. amazonensis promastigotes is present in the parasite and not in the culture supernatant (conditioned medium) (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%